Assessing Fear Following Retrieval + Extinction Through Suppression of Baseline Reward Seeking vs. Freezing - Shumake, Jason; Monfils, Marie H. (Frontiers in Behavioral Neuroscience, 2015)
Freezing has become the predominant measure used in rodent studies of conditioned fear, but conditioned suppression of reward-seeking behavior may provide a measure that is more relevant to human anxiety disorders; that is, a measure of how fear interferes with the enjoyment of pleasurable activities. Previous work has found that an isolated presentation of a fear conditioned stimulus prior to extinction training (retrieval + extinction) results in a more robust and longer-lasting reduction in fear. The objective of this study was to assess whether the retrieval + extinction effect is evident using conditioned suppression of reward seeking, operationalized as a reduction in baseline licking (without prior water deprivation) for a 10% sucrose solution. We found that, compared to freezing, conditioned suppression of reward seeking was much more sensitive to fear conditioning and far less responsive to extinction training. As in previous work, we found that retrieval + extinction reduced post-extinction fear reinstatement when measured as freezing, but it did not reduce fear reinstatement when measured as conditioned suppression. This suggests that there is still residual fear following retrieval + extinction, or that this procedure only modifies memory traces in neural circuits relevant to the expression of freezing, but not to the suppression of reward seeking.